The Search for Herbal Antibiotics: An In-Silico Investigation of Antibacterial Phytochemicals - Mary Snow Setzer; Javad Sharifi-Rad; William N. Setzer (MDPI AG, 2016)
Recently, the emergence and spread of pathogenic bacterial resistance to many antibiotics (multidrug-resistant strains) have been increasing throughout the world. This phenomenon is of great concern and there is a need to find alternative chemotherapeutic agents to combat these antibiotic-resistant microorganisms. Higher plants may serve as a resource for new antimicrobials to replace or augment current therapeutic options. In this work, we have carried out a molecular docking study of a total of 561 antibacterial phytochemicals listed in the Dictionary of Natural Products, including 77 alkaloids (17 indole alkaloids, 27 isoquinoline alkaloids, 4 steroidal alkaloids, and 28 miscellaneous alkaloids), 99 terpenoids (5 monoterpenoids, 31 sesquiterpenoids, 52 diterpenoids, and 11 triterpenoids), 309 polyphenolics (87 flavonoids, 25 chalcones, 41 isoflavonoids, 5 neoflavonoids, 12 pterocarpans, 10 chromones, 7 condensed tannins, 11 coumarins, 30 stilbenoids, 2 lignans, 5 phenylpropanoids, 13 xanthones, 5 hydrolyzable tannins, and 56 miscellaneous phenolics), 30 quinones, and 46 miscellaneous phytochemicals, with six bacterial protein targets (peptide deformylase, DNA gyrase/topoisomerase IV, UDP-galactose mutase, protein tyrosine phosphatase, cytochrome P450 CYP121, and NAD+-dependent DNA ligase). In addition, 35 known inhibitors were docked with their respective targets for comparison purposes. Prenylated polyphenolics showed the best docking profiles, while terpenoids had the poorest. The most susceptible protein targets were peptide deformylases and NAD+-dependent DNA ligases.